2022
DOI: 10.1108/el-08-2021-0161
|View full text |Cite
|
Sign up to set email alerts
|

Explaining student loyalty towards using WhatsApp in higher education: an extension of the IS success model

Abstract: Purpose Recent years have documented the growing interest in using WhatsApp in higher education. However, the determinants of students’ satisfaction and loyalty towards WhatsApp groups have received less attention. This study aims to extend the Delone and McLean information system success model by incorporating social and emotional factors to investigate the drivers of satisfaction. Design/methodology/approach Data were collected through questionnaires completed by 308 undergraduate students. The partial lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 126 publications
(158 reference statements)
3
9
0
Order By: Relevance
“…This can be used as a comparison and discussion material for future research. Iranmanesh et al [26] obtained a different result, showing that quality of information and trust is an important factors in shaping students' satisfaction and loyalty to WhatsApp. The quality of the system does not have a significant effect on satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…This can be used as a comparison and discussion material for future research. Iranmanesh et al [26] obtained a different result, showing that quality of information and trust is an important factors in shaping students' satisfaction and loyalty to WhatsApp. The quality of the system does not have a significant effect on satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Gaardboe et al (2017) in their study reported that a high information quality in terms of consistency, understanding, accuracy and relevance positively influences user satisfaction and user performance. An extensive amount of empirical proof can be found in the literature that information quality has a positive impact on user satisfaction and user performance (Al-Okaily et al, 2022a;Iranmanesh et al, 2022;Almajali et al, 2022). Drawing on these discussions, we hypothesize the following:…”
Section: Information Qualitymentioning
confidence: 91%
“…Faith in the actions of the source leads to positive outcomes, which will further increase satisfaction (Andaleeb, 1996). Many researchers agree that trust gives a sense of security and directly impacts customer satisfaction (Iranmanesh et al , 2022; Singh and Sirdeshmukh, 2000). Therefore, a higher level of trust in the community staff members means more satisfaction among the residents with the information service provided.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%